2012
DOI: 10.1097/mcg.0b013e31821f8bf6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrence After Resection of Small Gastric Gastrointestinal Stromal Tumors of 5 cm or Less

Abstract: Predictors of recurrence of gastric GISTs of 5 cm or less were a high mitotic index and abnormal p53 expression. A positive microscopic resection margin was not associated with recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…In the present study, although the small GISTs were ≤2 cm in size, the mitotic index of 6 small non-gastric GISTs was >5 mitoses per 50 HPF and the mitotic index of 2 out of 7 small GISTs (≤1 cm) was >5 per 50 HPF, which indicated the malignant potential and implied the necessity of surgical resection of small GISTs. No significant difference was identified between the mitotic index in the ≤1 cm diameter and 1–2 cm diameter groups, indicating that mitosis occurs in the early stage of disease, which is consistent with the findings of numerous studies in the literature ( 24 , 25 ). Gene detection was not performed in the present study, but a previous study by Corless et al ( 26 ) performed c-kit gene mutation testing on 13 small GISTs that were identified during autopsy or found incidentally, among which exon 11 (84.7%) was found to possess mutations of the c-kit gene.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, although the small GISTs were ≤2 cm in size, the mitotic index of 6 small non-gastric GISTs was >5 mitoses per 50 HPF and the mitotic index of 2 out of 7 small GISTs (≤1 cm) was >5 per 50 HPF, which indicated the malignant potential and implied the necessity of surgical resection of small GISTs. No significant difference was identified between the mitotic index in the ≤1 cm diameter and 1–2 cm diameter groups, indicating that mitosis occurs in the early stage of disease, which is consistent with the findings of numerous studies in the literature ( 24 , 25 ). Gene detection was not performed in the present study, but a previous study by Corless et al ( 26 ) performed c-kit gene mutation testing on 13 small GISTs that were identified during autopsy or found incidentally, among which exon 11 (84.7%) was found to possess mutations of the c-kit gene.…”
Section: Discussionsupporting
confidence: 90%
“…The management of GISTs is generally based on tumor size because biopsy is not recommended and mitotic index cannot be easily and accurately determined [13]. The National Comprehensive Cancer Network recommends surgical resection for tumors greater than 2 cm because of malignant potential, and lesions less than 2 cm can be conservatively followed up [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 articles, 2 were excluded due to the insufficient reported data for the estimation of HR, 3 were excluded because they put R1 resection and R2 resection together, and 2 were excluded due to the small sample size (there are only 2 cases with R1 margin in both studies) 17 18 . Finally, a total of 12 studies 14 15 16 19 20 21 22 23 24 25 26 27 were included in this meta-analysis. Literatures screening process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%